Corticofugal projection patterns of whisker sensorimotor cortex to the sensory trigeminal nuclei - Smith, Jared B.; Watson, Glenn D. R.; Alloway, Kevin D.; Schwarz, Cornelius; Chakrabarti, Shubhodeep (Frontiers in Neural Circuits, 2015)
The primary (S1) and secondary (S2) somatosensory cortices project to several trigeminal sensory nuclei. One putative function of these corticofugal projections is the gating of sensory transmission through the trigeminal principal nucleus (Pr5), and some have proposed that S1 and S2 project differentially to the spinal trigeminal subnuclei, which have inhibitory circuits that could inhibit or disinhibit the output projections of Pr5. Very little, however, is known about the origin of sensorimotor corticofugal projections and their patterns of termination in the various trigeminal nuclei. We addressed this issue by injecting anterograde tracers in S1, S2 and primary motor (M1) cortices, and quantitatively characterizing the distribution of labeled terminals within the entire rostro-caudal chain of trigeminal sub-nuclei. We confirmed our anterograde tracing results by injecting retrograde tracers at various rostro-caudal levels within the trigeminal sensory nuclei to determine the position of retrogradely labeled cortical cells with respect to S1 barrel cortex. Our results demonstrate that S1 and S2 projections terminate in largely overlapping regions but show some significant differences. Whereas S1 projection terminals tend to cluster within the principal trigeminal (Pr5), caudal spinal trigeminal interpolaris (Sp5ic), and the dorsal spinal trigeminal caudalis (Sp5c), S2 projection terminals are distributed in a continuum across all trigeminal nuclei. Contrary to the view that sensory gating could be mediated by differential activation of inhibitory interconnections between the spinal trigeminal subnuclei, , we observed that projections from S1 and S2 are largely overlapping in these subnuclei despite the differences noted earlier.